Mapping Arctic Research in Iceland (Icelandic Centre for Research, RANNÍS, 2020)
The scope of Arctic research in Iceland has been increasing during the past decade and the amount of grants allocated to Arctic research projects has risen. Mapping Arctic Research in Iceland contains an overview of governance of Arctic policy in Iceland and a profile of Arctic research performers, such as universities, institutes, companies and infrastructure. An analysis of both domestic and international funds supporting Arctic research is the main content of the report. Both domestic and international funds were examined, however the main focus was on the Icelandic Research Fund and EU Horizon 2020. Selected Arctic research projects with Icelandic participation and international platforms that serve Arctic-related issues are described.